PENGARUH TERAPI CERMIN TERHADAP KEMAMPUAN GERAK PADA PASIEN STROKE DI WILAYAH KERJA PUSKESMAS KUMPULAN KABUPATEN PASAMAN - Muhammad Arif; Suci Mustika; Def Primal (LPPM UNIVERSITAS PERINTIS INDONESIA, 2019)
Background: Stroke is a disease or functional disorder of the brain in the form of nerve paralysis due to inhibition of blood vassel flow to the brain. Based on Medikal Record data of Kumpulan Public Health Center 2016, there were 67 cases. Whereas in 2017 there were 81 cases of stroke 25 witch of them outpatients who experience weakness in the limb and have never received mirror therapy. Objective: This study was to investigate